(untitled) (Innovaciones Educativas, 2023)
Facing a scenario of unavoidable changes and a society that promotes the use of Information and Communication Technologies (ICT), the hybrid modality seeks to optimize traditional and virtual education. Therefore, the objective of the research was to evaluate the effectiveness of hybrid classes for the development of competencies in the subject of Quality Control in agro-industrial engineering students at a public university in Peru. Seventeen students enrolled in the 2022-I academic semester participated, who attended the hybrid classes through rotating and simultaneous classes, using synchronous technology (videoconference system with Zoom Rooms® software) and asynchronous technology (Microsoft Teams®). The instrument used was a 40-question Pedagogical Test of the Quality Control subject, divided into four dimensions that assess capabilities and was applied before and after the study. The results showed noticeable values, reaching learning levels of expected (47.1%), process (41.2%), expected (35.3%) and outstanding (47.1%) for the first, second, third and fourth ability, respectively. It is concluded that the hybrid classes were effective for the development of subject competencies with a p<0.05, which evidenced a significant difference between pretest and posttest. Likewise, 35.3% of students were in process and expected learning levels and 11.8% remained in beginning learning levels. Thus, there is a need for improvement in ICT access to continue strengthening the application of the hybrid modality.